Systematic Literature Review: Upaya Meningkatkan Kemampuan Berpikir Kreatif pada Pembelajaran Matematika - Lelia Suretdawati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to examine the efforts that can be made in improving creative thinking skills in mathematics learning. The method used is systematic literature review, consisting of three stages, namely planning, conducting, and reporting. The planning stage is the determination of protocols, including determining topics and determining article search criteria. The conducting stage is implementation, including article search, article selection, and data synthesis. The reporting stage is the final stage in systematic literature review, including writing the results of systematic literature review in accordance with a predetermined format. Based on the study of 15 international articles and 5 national articles, the application of the Problem Based Solving learning model is the most widely made effort to improve creative thinking skills. In addition to Problem Based Learning, there are several efforts that can be made to improve creative thinking skills, including by applying Open Ended, Open Inquiry, Project Based Learning, Resource Based Learning, Creative Problem Solving, Realistic Mathematics, or Guided Inquiry in mathematics learning.